Blended learning: examining student satisfaction, willingness, and stress in learning English / Nurul Yasmin Mohamad Yusof - Mohamad Yusof, Nurul Yasmin (2014)
Blended learning is increasingly applied in the educational system. This form of learning which combines face-to-face classroom learning with some technological aids has been widely used in teaching and learning, making it suitable to be applied in learning English. The purpose of this study is to examine student practices of learning through blended learning approach have on student satisfaction, willingness and stress in learning English. It also investigates the correlation between student quality of learning and their level of satisfaction, willingness and stress in respect to the learning approach in a blended learning environment. A quantitative approach was employed as an instrument. A survey was designed to gather valid data about the concerned study. Semi-structured interviews were also conducted to support the findings from the questionnaire. The questionnaire was completed by 137 students who were selected using random sampling technique. The results revealed that students possess positive quality of learning indicated by a high level of satisfaction and willingness and low stress level. Moreover, no statistically significant difference existed in the student satisfaction and stress of blended learning approach due to gender variable. However, time was found to have significant variable affecting student willingness towards blended learning. In overall, the study concluded that blended learning is suitable to be applied in language classroom because it helps students to learn English effectively.